Analysis of the Antibacterial Activity and the Total Phenolic and Flavonoid Contents of the Moringa oleifera Leaf Extract as an Antimicrobial Agent against Pseudomonas aeruginosa - Ahmad Royani; Muhammad Hanafi; Puspa Dewi N. Lotulung; Heddy Julistiono; Achmad Dinoto; Azwar Manaf (Scientifica, 2023)
Pseudomonas aeruginosa is a bacterium that causes metal deterioration by forming biofilms on metal surfaces. This work was carried out to analyze the antibacterial activity and the phenolic and flavonoid contents of the Moringa oleifera leaf extract against Pseudomonas aeruginosa. M. oleifera leaves were extracted in a methanol solution at different concentrations. The M. oleifera leaf extract yields were 12.84%, 18.96%, and 19.64% for the 100%, 75%, and 50% methanol ratios, respectively. Extracts of M. oleifera leaves had a minimum inhibiting concentration (MIC) of approximately 6144 μg/mL against P. aeruginosa for a ratio of 100% methanol. In addition, no antibacterial activity was found for the 75% and 50% methanol ratios. The total phenolic levels were 16.26%, 12.73%, and 12.33% for the 100%, 75%, and 50% methanol solvent ratios, respectively. The total amounts of flavonoids were 23.32%, 3.40%, and 0.64% for the 100%, 75%, and 50% methanol solvents, respectively. The chemical structure of M. oleifera consists of kaemferol-3-O-rutinoside, quercimeritrin, kaempferol-3-O-β-D-glucopyranoside, stearidonic acid, trichosanic acid, pyrophaeophorbide A, and stigmastan-3,6-dione. The concentration of the solvent is essential in the extraction of plant constituents. Different concentrations indicate differences in antibacterial activity, phenolic and flavonoid contents, and chemical structure.